The Legal Regulation of Private Education within the Ministry of Education - Shendi Habib Shalal Al-Simri, Assist. Lect . Alia (Basra studies journal, 2025)
This research highlights the legal regulations governing the procedures for establishing, managing, and supervising private educational institutions under the jurisdiction of the Iraqi Ministry of Education. It focuses on the provisions of the Private and Foreign Education System No. (5) of 2013 and examines the adequacy of these rules in regulating the process in a manner that ensures full legal legitimacy. The study also explores how these institutions are monitored, identifies the entities responsible for exercising supervisory authority, assesses the effectiveness of their oversight, and analyzes the legal framework adopted for this purpose.